Composition of Essential Oils in Turmeric Rhizome - Devkota, Laxmi; Rajbhandari, Meena (Nepal Journal of Science and Technology, 2016)
Turmeric has been recognized as a pharmaceutical crop. It is valuable primarily for essential oil and curcumin content. Chemical composition of the essential oils obtained from the rhizome of turmeric was determined by GC/MS technique. More than 75 compounds were detected and 67 of them were identified. They accounted for 98.59% of essential oil. The essential oil contained 15 monoterpenes (5.58%), 43 sesquiterpenes (84.37%) and 10 nonterpenic components (8.64%). The major constituents were ß-turmeron, a-turmeron, Epi-a-patschutene, ß-sesquiphellandrene, 1,4-dimethyl-2-isobutylbenzene, (±)-dihydro-ar-turmerone, zingiberene, E-a-atlantone and (-)-caryophyllene oxide. Thin layer chromatographic finger printing and quantitative determination of phenolics in acetone extract of commercially available turmeric samples were carried out using Folin-Ciocalteu colorimetric method. Gallic acid was used as the standard for the estimation of phenolics. All the investigated turmeric extracts contained relatively high amount of phenolics. Nepal Journal of Science and Technology Vol. 16, No.1 (2015) pp. 87-94